2022
DOI: 10.1039/d1na00570g
|View full text |Cite
|
Sign up to set email alerts
|

Organic contaminants and atmospheric nitrogen at the graphene–water interface: a simulation study

Abstract: Formation of hydrocarbon monolayers at the graphene–water interface can be predicted from the concentration in ambient air and the free energies of hydration, adsorption from the aqueous phase, and subsequent integration into the monolayer phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 68 publications
(190 reference statements)
2
22
0
Order By: Relevance
“…These distances are not consistent with other possible constituents such as polyaromatic compounds, which exhibit smaller interlayer distances. 17,20 The results indicated that hydration layers were initially formed on a pristine graphite surface. However, those layers were replaced over time by 2-3 layers of alkane-like hydrocarbons likely originating from the air.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…These distances are not consistent with other possible constituents such as polyaromatic compounds, which exhibit smaller interlayer distances. 17,20 The results indicated that hydration layers were initially formed on a pristine graphite surface. However, those layers were replaced over time by 2-3 layers of alkane-like hydrocarbons likely originating from the air.…”
Section: Resultsmentioning
confidence: 98%
“…While MD simulations have indicated that distances of 0.45 nm are characteristic of well-ordered straightchain alkane layers, small amounts of branching, heteroatom substitution, or cyclic moieties led to slightly larger interlayer distances of 0.47-0.52 nm. 17,20 Furthermore, the simulations revealed that the tails of straight-chain alkanes sometimes extend out-of-plane, forming defects in the layer that disrupt the structure of layers above and slightly increase the interlayer distance. Hence, defects in the lower layers cumulatively make the third layer more disordered and d 2 slightly larger than d 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 Our simulations have also predicted that water molecules in this first solvation layer exhibit a mild tendency to orient parallel to the graphene sheet. 47 Therefore, the solvation structure around the planar β-sheet is quite different from a regular β-sheet in solution. Figure 11 A shows regions of high water density around the peptide CHP1404.…”
Section: Resultsmentioning
confidence: 99%